THU0258 N-terminal pro-brain natriuretic peptide in a novel screening algorithm for pulmonary arterial hypertension in systemic sclerosis. (23rd January 2014) - Thakkar, V.; Stevens, W.; Prior, D.; Moore, O.; Byron, J.; Patterson, K.; Hissaria, P.; Roddy, J.; Zochling, J.; Sahhar, J.; Nash, P.; Tymms, K.; et al.
Abstract : Background: Pulmonary Arterial Hypertension (PAH) is a major cause of mortality in SSc. N-terminal pro-brain natriuretic peptide (NT-proBNP) has emerged as a candidate biomarker that may enable the early detection of systemic sclerosis-related pulmonary arterial hypertension (SSc-PAH). Objectives: To incorporate N-terminal pro-brain natriuretic peptide (NT-proBNP) into a screening algorithm for systemic sclerosis-related pulmonary arterial hypertension (SSc-PAH) that could potentially replace transthoracic echocardiography (TTE) as a less costly and more convenient "first tier" test. Methods: NT-proBNP levels were measured in patients from 4 clinical groups: a group with right heart catheter (RHC) diagnosed SSc-PAH prior to commencement of therapy for PAH; a group at high risk of SSc-PAH based on TTE; a group with interstitial lung disease; and systemic sclerosis (SSc) controls with no cardiopulmonary complications. NT-proBNP levels were compared using ANOVA and correlated with other clinical variables using simple and multiple linear regression. ROC curve analyses were performed to determine the optimal cut-point for NT-proBNP and other clinical variables in prediction of PAH. Results: NT-proBNP was highest in the PAH group compared to other groups (p<0.0001), and higher in the risk group compared to controls (p<0.0001). NT-proBNP was positively correlated with systolic pulmonary artery pressure (PAP) on TTE (p<0.0001), and mean PAP (p=0.008), pulmonary vascular resistance (p=0.001) and mean right atrial pressure (p=0.006) on RHC. A composite model wherein patients screened positive if NT-proBNP ≥209.8pg/ml, and/or DLCOcorr <70.3% with FVC/DLCOcorr ≥1.83, had a sensitivity of 100% and specificity of 77.8% for SSc-PAH. Conclusions: We have proposed a screening algorithm for SSc-PAH, incorporating NT-proBNP level and PFTs. This model has high sensitivity and specificity for SSc-PAH and if positive, should lead to TTE and confirmatory testing for PAH. This screening algorithm needs to be validated prospectively. Disclosure of Interest: None Declared